IMPLEMENTASI PENDEKATAN EDUKATIF-KREATIF BERBASIS AYAT AL-QUR’AN FAVORIT UNTUK MENINGKATKAN LITERASI AL-QUR’AN ANAK TPQ AL-MAGHFIROH BANDAR PUTIH LAMPUNG TENGAH - Dessy Kurnia Mulyani; Marleni Marleni; Melli Indah Novitasari; Muhammad Iqbal (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
Qur’anic literacy is a fundamental competence in Islamic education that encompasses the ability to read the Qur’an correctly according to makhraj and tajwid, reading fluency, and proper manners in interacting with the Qur’an. Early Qur’anic education plays a strategic role in shaping children’s religious character, discipline, and spiritual attitudes. However, Qur’anic learning in non-formal educational institutions such as Taman Pendidikan Al-Qur’an (TPQ) often faces challenges, particularly low learning interest and motivation among students due to the use of monotonous and teacher-centered instructional approaches. This article aims to describe the implementation of an educative-creative approach based on favorite Qur’anic verses in enhancing Qur’anic literacy among children at TPQ Al-Maghfiroh, Bandar Putih Tua Village, Central Lampung. The study employed a descriptive qualitative approach supported by quantitative data obtained through pre-test and post-test assessments. The findings indicate an improvement in children’s Qur’anic literacy, including reading fluency, accuracy of makhraj and basic tajwid, as well as learning motivation and engagement. The educative-creative approach based on favorite Qur’anic verses can serve as an effective, enjoyable, and developmentally appropriate model for Qur’anic learning.